(untitled) (Bangladesh Journal of Agricultural Research, 2020)
The present experiment was conducted to optimize protocols for in vitro propagation of banana (Musa sp.) cv. ‘Patakpura’ (AAB), supplemented with different growth regulators. Shoot tips obtained from sword suckers were cultured aseptically on MS medium supplemented with different concentrations of cytokinins like 6-Benzylaminopurine (BAP) and Kinetin (KN) for multiplication of shootsand auxins such as indole acetic acid (IAA) and naphthalene acetic acid (NAA) for induction of roots. The best result from the initial culture was obtained from MS medium supplimented with 4 mg/l BAP + 0.5 mg/l IAA. The highest shoot fresh weight, shoot length and number of shoots per explant were recorded from MS medium supplemented with 4 mg/l BAP + 0.5 mg/l IAA + 0.25 mg/l NAA. Therefore, the MS medium supplemented with 4 mg/l BAP + 0.5 mg/l IAA + 0.25 mg/l NAA was found to be most effective and productive combination for shoot multiplication and proliferation of the culture in vitro. IAA at a concentration of 1 mg/l was found to be most suitable for rooting of the shoots. Bangladesh J. Agril. Res. 44(4): 641-648, December 2019